Institutionalizing Internal Audit in Indonesian Startups: Regulatory Alignment and Fraud Prevention Strategies - Prayoga, Cepi Juniar; Sukristanta (Indonesian Scientific Publication, 2025)
This study investigates the role of internal audit systems in preventing fraud within Indonesian technology startups, emphasizing their vulnerability due to underdeveloped governance structures and exploring how regulatory frameworks and internal mechanisms can mitigate these risks. Using a qualitative approach that combines regulatory analysis, literature review, and case study evaluation, the research triangulates Indonesian regulatory documents (PP 71/2019, UU PDP 27/2022, POJK 40/2024), ACFE global fraud reports, and case evidence from eFishery, Investree, and TaniFund to examine audit failures and formulate best practices. The findings reveal that financial constraints, cultural attitudes, and limited audit knowledge hinder the effective implementation of internal audit systems, while whistleblowing mechanisms—though essential—require integration with formal audit processes to deliver meaningful impact. Case analyses further confirm that audit deficiencies contribute to regulatory sanctions and operational instability, underscoring the importance of adopting maturity models (e.g., COSO, IA CM) and analytics-driven continuous auditing to enhance responsiveness. Overall, the study concludes that internal audit should be positioned as a strategic enabler rather than a mere compliance obligation; when integrated with whistleblowing channels and supported by audit maturity frameworks, it can significantly reduce fraud exposure, strengthen governance, and foster sustainable growth in technology startups across emerging markets.